Masked polycythemia Vera (mPV): Results of an international study. Issue 1 (19th September 2013) - Barbui, Tiziano; Thiele, Jürgen; Gisslinger, Heinz; Finazzi, Guido; Carobbio, Alessandra; Rumi, Elisa; Luigia Randi, Maria; Betozzi, Irene; Vannucchi, Alessandro M.; Pieri, Lisa; Carrai, Valentina; Gisslinger, Bettina; et al.
<x xml:space="preserve">Abstract</x> We examined the baseline features and clinical outcomes of 140 patients presenting with JAK2V617F positivity and a bone marrow morphology conforming with WHO criteria of polycythemia vera (PV), but a hemoglobin level of <18.5 g/dL in males (range 16.0–18.4) and <16.5 g/dL in females (range 15.0–16.4). This cohort operationally referred to as masked PV (mPV) was compared with 257 patients with overt PV and displayed male predominance, a more frequent history of arterial thrombosis and thrombocytosis. Incidence of thrombosis was similar between the two groups but mPV displayed significantly higher rates of progression to myelofibrosis and acute leukemia and inferior survival. In multivariable analysis mPV diagnosis was an independent predictor of poor survival along with age >65 years and leukocyte count >10 × 109/L. Our data suggest that mPV is a heterogeneous myeloproliferative neoplasia and not necessarily an early/ pre‐polycythemic form of classical PV that at onset in a small fraction of patients clinically may mimic essential thrombocythemia. On the other hand, the majority mPV may have a longer prodrome of undiagnosed PV or a disease biology akin to primary myelofibrosis‐post PV myelofibrosis that could explain the worsening of outcome in comparison to overt/classical manifestations. Am. J. Hematol. 89:52–54, 2014. © 2013 Wiley Periodicals, Inc.